2013
DOI: 10.2134/jeq2013.06.0219
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide and Nitrate Trends in Domestic Wells where Pesticide Use Is Regulated in Fresno and Tulare Counties, California

Abstract: The California Department of Pesticide Regulation initiated regulations on pesticide use in 1989 to mitigate groundwater contamination by atrazine [6‐chloro‐N‐ethyl‐N′‐(1‐methylethyl)‐1,3,5‐triazine‐2,4‐diamine] and subsequently for simazine (6‐chloro‐N,N′‐diethyl‐1,3,5‐triazine‐2,4‐diamine), diuron [N′‐(3,4‐dichlorophenyl)‐N,N‐dimethylurea], bromacil [5‐bromo‐6‐methyl‐3‐(1‐methylpropyl)‐2,4(1H,3H)‐pyrimidinedione], and norflurazon [4‐chloro‐5‐(methylamino)‐2‐[3‐(trifluoromethyl)phenyl]‐3(2H)‐pyridazinone]. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…6). This region includes a significant portion of "runoff" designated GWPA zones on soils that contain a shallow hardpan layer (Troiano et al, 2014) and where dry wells used for surface drainage are common (DeMartinis and Royce, 1990). In addition, the water table in these same regions is relatively shallow (7-10 m b.g.s.)…”
Section: Discussionmentioning
confidence: 99%
“…6). This region includes a significant portion of "runoff" designated GWPA zones on soils that contain a shallow hardpan layer (Troiano et al, 2014) and where dry wells used for surface drainage are common (DeMartinis and Royce, 1990). In addition, the water table in these same regions is relatively shallow (7-10 m b.g.s.)…”
Section: Discussionmentioning
confidence: 99%
“…It is usually found in literature studies with materials that remove one or two of these contaminants 22,[38][39][40][41] . However, considering that it is common to find several contamination forms in drinking water and not just one, studying a material with multi-pollutant removal potential is extremely valuable, since it could make the water treatment process simpler and more cost-effective [42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies in the San Joaquin Basin, Sacramento Valley and other counties have already confirmed high levels of nitrate in the groundwater of the CV [14][15][16][17][18]. Statistical methods have been used to study the relationship between groundwater nitrate contamination and predictor variables.…”
Section: Introductionmentioning
confidence: 99%